Screening Hipertensi pada Lansia Di Wilayah Puskesmas Banyumas - Sri Suparti; Diyah Yulistika Handayani (Universitas Muhammadiyah Ponorogo, 2019)
Abstract Hypertension in the elderly is abnormally high blood pressure where the systolic pressure is above ≥140 mmHg and diastolic pressure above ≥90 mmHg is measured at least on three different occasions. Hypertension is a chronic disease that can not be cured but can be controlled. Hypertension in elderly increases with age and degenerative proceses. This study aims to determine the description of Hypertension Screening in Elderly. The design used of this research was descriptive analytic research using crossectional approach, sampling technique using cluster sampling with random. Data collection instrument used a questionnaire screening the risk of hypertension and measurement of blood pressure used sphygnomanometer. The analysis used Chi Square statistical test with significance level 0,05. The results showed that respondents who risked suffering from hypertension as much as 107 (52.2%) did not have hypertension and 98 (47.8) were at risk of hypertension. There was no relationship between age, sex, marital status and risk of hypertension with consecutive values of 0.530, 0.434 and 0.508. Screening of Hypertension can be done as early detection to determine the health status of elderly patients.